Study on Seasonal Variation of Cohesive Suspended Sediment Transport in Estuary of Mahakam Delta by using A Numerical Model - Safwan Hadi; Nining Sari Ningsih; Ayi Tarya (Jurnal Teknik Sipil, 2006)
Abstract. A coupled three-dimensional hydrodynamics and sediment transport model of HydroQual, Inc., (2002), ECOMSED, has been used to simulate variation of suspended cohesive sediment transport in Estuary of Mahakam Delta. The simulation results indicate that tides and seasonal variation of river discharges are the main causes of variations in the suspended sediment concentration in this area. A one-year simulation of suspended sediment distribution shows that the suspended cohesive sediment discharge to the Makassar Strait is mainly transported southward, namely through locations of Muara Jawa and Muara Pegah and seems to reach a maximum distance of distribution in January and a minimum one in October. The simulation results also show that river discharges less influence the suspended sediment concentration at Tanjung Bayur, which is located at the tip of the channel in the middle, compared to the other locations. Abstrak. Suatu model kopel tiga dimensi hidrodinamika dan transpor sedimen HydroQual, Inc., (2002), ECOMSED, diterapkan untuk mensimulasi variasi transpor sedimen kohesif melayang di Estuari Delta Mahakam. Hasil simulasi menunjukkan bahwa pasut dan variasi musiman dari debit sungai adalah penyebab utama dari variasi konsentrasi sedimen melayang di daerah ini. Simulasi satu tahun distribusi sedimen melayang memperlihatkan bahwa sedimen kohesif yang memasuki Selat Makassar terutama ditransporkan ke arah selatan melalui Muara Jawa dan Muara Pegah. Jangkauan maksimum dari aliran sedimen memasuki Selat Makassar terjadi pada bulan Januari dan minimum pada bulan Oktober. Hasil simulasi juga menunjukkan bahwa pengaruh debit sungai terhadap konsentrasi sedimen di Tanjung Bayur lebih kecil daripada di lokasi-lokasi yang lain.